2015
DOI: 10.23986/afsci.49729
|View full text |Cite
|
Sign up to set email alerts
|

Phytic acid, inorganic phosphorus, antioxidants in bread and durum wheat and their associations with agronomic traits

Abstract: The phytic acid (PA), inorganic phosphorus (Pi), yellow pigment (YP), water soluble phenolics (WSPH) and free protein sulfhydryl groups (PSH) of 15 Triticum aestivum and 15 Triticum durum wheats grown at six different environments were evaluated for variability, intra- and inter- relations with agronomic traits. The most variable properties in bread wheat were YP and WSPH with coefficients of variation (CV) amounting to 14.59% and 14.10%, respectively, while in durum wheat those were PSH and YP with CV of 17.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…The variation found for phytic acid ranged from 0.462 to 0.952% (2-fold variation) in the whole trial, with an average of 0.675%. Branković et al (2015) reported a smaller range of variation for phytic acid but with significantly higher values (1.463–1.678%) in a set of 15 durum genotypes (nine with CIMMYT origin), which shows the importance of the environmental conditions and methodology used when dealing with this trait. Tabekha and Donnelly (1982) also found higher values in six durum cvs.…”
Section: Discussionmentioning
confidence: 93%
“…The variation found for phytic acid ranged from 0.462 to 0.952% (2-fold variation) in the whole trial, with an average of 0.675%. Branković et al (2015) reported a smaller range of variation for phytic acid but with significantly higher values (1.463–1.678%) in a set of 15 durum genotypes (nine with CIMMYT origin), which shows the importance of the environmental conditions and methodology used when dealing with this trait. Tabekha and Donnelly (1982) also found higher values in six durum cvs.…”
Section: Discussionmentioning
confidence: 93%
“…The two remaining compounds belonged to flavanols (catechin hydrate), a specific class of flavonoids, and to phenolic aldehydes (syringaldehyde). Most of these compounds were already identified in previous durum wheat investigations in both grains and shoot tissues (Branković et al, ; Di Loreto et al, ; Pasqualone et al, ; Shamloo et al, ; Stagnari et al, ).…”
Section: Discussionmentioning
confidence: 68%
“…Few O 3 experiments have been conducted on the mechanisms of the secondary metabolism of wheat cultivars, and little is known of the role played by phenolic compounds in the ROS scavenging and antioxidant mechanism (Fatima, Singh, Mukherjee, Agrawal, & Agrawal, ; Wang, Zhu, Zheng, & Liu, ; Yadav et al, ). More generally, also few studies have investigated the phenolic metabolism of durum wheat, only focusing on grain contents (Branković et al, ; Di Loreto et al, ; Pasqualone et al, ; Shamloo et al, ), except for the work of Stagnari et al () where sprouts and wheatgrass (about 5 and 12 cm shoot length, respectively) of T. durum cultivar Creso were also assessed. Thus, the major value of the present study is undoubtedly the pioneering investigation of phenolic metabolism of durum wheat under O 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, wheat genotypes with low phytate and high mineral concentration could be immensely useful in breeding programs that aim to develop biofortified verities for essential mineral nutrients. Many studies have analyzed the variability of phytate content among wheat cultivars and germplasm lines (60)(61)(62). The analysis of phytic acid content of a set of 65 bread varieties of Pakistan showed variation in the range 0.706-1.113% (60).…”
Section: Phytate Contentmentioning
confidence: 99%